Analisis Faktor-Faktor yang Mempengaruhi Nilai Informasi Pelaporan Keuangan Pemerintah Daerah - Eko Prasetyo (Journal of Applied Accounting and Taxation, 2017)
Financial management of regional governments must be based on good governance goverment, that financial management is conducted transparently and accountably. Public financial management. UU No.17/2013 regulates the state finances which requires the form and content of the accountability report. One form of accountability report is the government's financial statements. Based on PP 17/ 2010, the reliability of financial reporting is the information in the financial statements. This type of research is descriptive quantitative research. The population in this study are all the Head of Department, Head of the Section and District Government Kasubbagian in Muaro, the sample used is as much as 83 respondents. This analytical tool used to determine the effect of the application of financial supervision, internal control systems, human resources, and the use of technology affect the value of local financial reporting information by using multiple linear regression. The results showed that the area of financial supervision, internal control systems, human resources, information technology influence simultaneously on the value of the local government financial reporting information, financial supervision only partially affect the indigo area of financial reporting information.